2010
DOI: 10.1021/ol100172w
|View full text |Cite
|
Sign up to set email alerts
|

Reaction-Based Sensing of Fluoride Ions Using Built-In Triggers for Intramolecular Charge Transfer and Photoinduced Electron Transfer

Abstract: Two Bodipy derivatives with silyl-protected phenolic functionalities signal fluoride concentrations both in solution and in a poly(methyl methacrylate) matrix. The exact location of the "nascent" phenolate group is important. If it is at the meso position, photoinduced electron transfer is triggered; however, if it is in full conjugation via a styryl moiety to the Bodipy core, strong intramolecular charge transfer is triggered, resulting in a large red shift in the absorbance peak. In either case, a selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(76 citation statements)
references
References 47 publications
(10 reference statements)
0
76
0
Order By: Relevance
“…[60] ICT has been discussed with BODIPY-linked phenol and anisole, as well, where the oxygen is the electron donating group. [61,[64][65][66] However, the emission maximum of these compounds was found to be solvent independent. Fluorescence emission intensities decreased with increasing pH suggesting a non-emissive excited state of the phenoxide anion due to very efficient ICT.…”
Section: Discussion Of Outliersmentioning
confidence: 96%
“…[60] ICT has been discussed with BODIPY-linked phenol and anisole, as well, where the oxygen is the electron donating group. [61,[64][65][66] However, the emission maximum of these compounds was found to be solvent independent. Fluorescence emission intensities decreased with increasing pH suggesting a non-emissive excited state of the phenoxide anion due to very efficient ICT.…”
Section: Discussion Of Outliersmentioning
confidence: 96%
“…Similar changes was also observed upon the stepwise addition of AcO -and H 2 PO 4 -( Figure S6 and S7), respectively. Such quenching can be attributable to the occurrence of ICT quenching the exited state of BODIPY moiety by the phenolate salt 22 . It was found that 1 demonstrated fluorescence quench in varying degrees, which was 97-fold for F -, 10-fold for AcO -and 5-fold for H 2 PO 4 -in Figure 7.…”
Section: Fluorescence Spectramentioning
confidence: 99%
“…Where 3 shows the special selectivity for F -through color change and fluorescence quenching, the hindrance of tert-butyl groups and the fitness of Brønsted acid-base are responsible for selective F -recognition over other tested anions. To our knowledge, both PET and ICT processes could lead to different optical output 22,23 . We therefore wonder if phenol unit can be introduced at C(3)-position of BODPIY by a vinyl spacer to acquire an ICT-based anion sensor.…”
Section: Introductionmentioning
confidence: 96%
“…Remarkable progress has been made since then in the development of molecular logic gates [2][3][4][5][6][7][8][9][10][11][12][13][14]. The change in fluorescence characteristics of a dye due to the introduction of some external agent can be considered to be analogous to the digital responses in electronic logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…Basic logic operation of a molecular logic gate is the same as that of the electronic one, the only difference is in the input and output signal. Nowadays, these molecular logic gates can be used as simple as well as more complex devices [17][18][19] such as adders and subtractors [2][3][4], multiplexers/demultiplexers [5][6][7], encoders/decoders [8,9], keypad locks [10][11][12][13][14] etc. Among many applications of molecular logic gates, one of the most interesting is the investigation of the inside components of a cell, where silicon-based analogues are not expected to reach [2].…”
Section: Introductionmentioning
confidence: 99%